Cysteine deleted protegrin-1 (CDP-1) : anti-bacterial activity, outer-membrane disruption and selectivity - Mohanram, Harini (2015)
BACKGROUND: Protegin-1 (PG-1: RGGRLCYCRRRFCVCVGR-amide) assumes a rigid β-hairpin like structure that is stabilized by two disulfide bridges between Cys6-Cys15 and Cys8-Cys13. Previous studies, employing linear analogs of PG-1, with Cys to Ala mutations or modified Cys, have demonstrated that the disulfide bridges are critical for the broad spectrum and salt resistant antimicrobial activity of PG-1. METHODS: In order to understand structural and functional roles of disulfide bonds in protegrins, we have synthesized a Cys deleted variant of PG-1 or CDP-1, RGGRLYRRRFVVGR-amide, and two of its analogs, RR11, RLYRRRFVVGR-amide, and LR10, LYRRRFVVGR-amide, containing deletion of residues at the N-terminus. These peptides have been characterized for bactericidal activity and mode of action in lipopolysaccharide (LPS) using optical spectroscopy, ITC and NMR. RESULTS: Antibacterial activity, against Gram-negative and Gram-positive strains, of the three peptides follows the order: CDP-1>RR11>LR10. LR10 displays only limited activity toward Gram-negative strains. CDP-1 demonstrates efficient membrane permeabilization and high-affinity interactions with LPS. CDP-1 and RR11 both assume β-hairpin like compact structures in complex with LPS, whereas LR10 adopts an extended conformation in LPS. In zwitterionic DPC micelles CDP-1 and the truncated analog peptides do not adopt folded conformations. MAJOR CONCLUSIONS: Despite the absence of stabilizing disulfide bridges CDP-1 shows broad-spectrum antibacterial activity and assumes β-hairpin like structure in complex with LPS. The β-hairpin structure may be essential for outer membrane permeabilization and cell killing.